Evanescent wave absorption sensor with direct-growth MoS2 film based on U-bent tapered multimode fiber - Li, Zhe; Zhang, Chao; Han, Yanshun; Gao, Saisai; Sheng, Yingqiang; Zhang, Suzhen; Lu, Zhengyi; Man, Baoyuan; Jiao, Yang; Jiang, Shouzhen (Journal of physics. D, Applied physics, 2017)
In this work, we presented a novel evanescent wave absorption sensor based on U-bent tapered multimode fiber covered by molybdenum disulfide (MoS2) film (MoS2@TU fiber EWA sensor). The multimode fiber was manufactured by the fused tapered fiber machine, and then heated using a butane candle flame and bent into a U-bent structure. MoS2 was grown on the fiber directly by thermally decomposing the precursor of (NH4)2MoS4. We have demonstrated that the MoS2 can be applied in the filed of EWA sensor, and the EWA sensor based on U-bent tapered multimode fiber (TU fiber) possessed higher sensitivity than that based on U-bent fiber. The sensitivity (ΔA/ΔC) of the developed EWA sensor is 0.34 in detection of ethanol solution. It shows good sensitivity, linearity, repeatability and stability in detection. And the developed EWA sensor also shows good performance in detection of the adenosine solution, this work shows that the developed EWA sensor may have promising applications in biosensing.